A large-scale study on the nocturnal behavior of African ungulates in zoos and its influencing factors - Gübert, Jennifer; Hahn-Klimroth, Max; Dierkes, Paul W. (Frontiers in Ethology, 2023)
Introduction The nocturnal behavior of many ungulate species has currently not been sufficiently studied. However, the behavioral patterns of large herbivores vary greatly between day and night, and knowledge about species’ behavior is not only scientifically interesting, but also required for successful animal management and husbandry. Material and methods In the current study, the nocturnal behavior of 196 individuals of 19 ungulate species in 20 European zoos is studied, providing the first description of the nocturnal behavior of some of the species. The importance of a wide range of possible factors influencing nocturnal behavior is discussed. Specifically, the behavioral states of standing and lying were analyzed, evaluating the proportion and number of phases in each behavior. The underlying data consist of 101,629 h of video material from 9,239 nights. A deep learning-based software package named Behavioral Observations by Videos and Images Using Deep-Learning Software (BOVIDS) was used to analyze the recordings. The analysis of the influencing factors was based on random forest regression and Shapley additive explanation (SHAP) analysis. Results The results indicate that age, body size, and feeding type are the most important factors influencing nocturnal behavior across all species. There are strong differences between the zebra species and the observed Cetartiodactyla as well as white rhinos. The main difference is that zebras spend significantly less time in a lying position than Cetartiodactyla. Discussion Overall, the results fit well into the sparse existing literature and the data can be considered a valid reference for further research and might help to assess animal's welfare in zoos.